EDUKASI PARTISIPATIF PENGENDALIAN HAMA TIKUS DI LAHAN PERSAWAHAN KECAMATAN TAMBAN CATUR KABUPATEN KAPUAS KALIMANTAN TENGAH - Tuti, Harlina Kusuma; Sepe, Muslimin; Romadhan, Panji; Rido, Muhammad; Putripertiwi, Dwija; Regina, Nur inayah Alfi (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Rice is a major staple food in Indonesia that often faces serious challenges from rice field rats (Rattus argentiventer), which can cause yield losses of up to 20–25%, and in severe cases, lead to crop failure. This community service program aimed to enhance farmers’ capacity in controlling rice field rats through a participatory education approach in Sido Mulyo Village, Tamban Catur Subdistrict, Kapuas Regency, Central Kalimantan. The program was conducted on August 19–20, 2024, using training, mentoring, and counseling methods involving farmers actively from planning to evaluation stages. The materials covered identification of rat species, symptoms of infestation at various rice growth stages, and environmentally friendly control techniques such as mass hunting, Trap Barrier System (TBS) installation, utilization of natural predators, and habitat sanitation. The results showed improved farmers’ knowledge and skills in mapping rat burrows, recognizing infestation symptoms, and implementing integrated and simultaneous control measures. The participatory approach also fostered awareness of the importance of collective action among farmers to ensure sustainable rice production. This program is expected to serve as a model for sustainable rat control in other rice-producing areas.